Butyrate inhibits pro-proliferative miR-92a by diminishing c-Myc-induced miR-17-92a cluster transcription in human colon cancer cells. Issue 1 (December 2015) - Hu, Shien; Liu, Lan; Chang, Eugene; Wang, Jian-Ying; Raufman, Jean-Pierre
Abstract Background Compromised colonic butyrate production resulting from low dietary fiber or altered gut microbiota may promote colon neoplasia. Previous reports indicate these actions are mediated in part by altered levels of miRNAs, including suppressed expression of the oncogenic miR-17-92a cluster. Here, we sought to identify the mechanisms underlying these effects of butyrate in colon cancer. Methods miR-92a levels were measured in archived human colon cancer and adjacent normal colon specimens by microarray and quantitative RT-PCR (qPCR). The effects of butyrate and other histone deacetylase inhibitors (suberoylanilide hydroxamic acid (SAHA) and valproic acid) on primary (pri-miR17-92a), precursor and mature miR-92a were analyzed in HCT-116 and HT-29 human colon cancer cells using qPCR. The effects of butyrate, SAHA and valproic acid on protein levels of c-Myc, Drosha and p57 were measured in HCT-116 cells using immunoblotting. Regulation of C13orf 25 promoter activity by butyrate was analyzed by luciferase reporter assay using modified pGL3 constructs containing a wild-type or mutated c-Myc binding site. Expression of c-Myc was modulated using siRNA or adenovirus vectors. p57 mRNA and protein were measured before and after transfection with miR-92a-mimic molecules. Following butyrate treatment and miR-92a-mimic transfection, apoptosis was analyzed by TUNEL staining and caspase-3 immunoblotting. Results Microarray, confirmed by qPCR, revealed a seven-fold increase in miR-92a levels in sporadic human colon cancer tissue compared to adjacent normal colon. Treating human colon cancer cells with butyrate reduced the levels of pri-miR17-92a, precursor and mature miR-92a, as well as c-Myc. SAHA and valproic acid had similar effects. Mutation of the c-Myc binding site diminished butyrate's inhibitory effects on C13orf 25 promoter activity. Silencing c-Myc expression reduced miR-92a levels. c-Myc over-expression neutralized butyrate-induced attenuation of pri-miR17-92a. Exogenous miR-92a inhibited butyrate-induced p57 expression and reversed the beneficial actions of butyrate on colon cancer cell proliferation and apoptosis. Conclusions Our findings identify a novel cellular mechanism whereby butyrate inhibits miR-92a transcription by reducing c-Myc, thus augmenting p57 levels. These actions diminish colon cancer cell proliferation and stimulate apoptosis. This newly described regulation of oncogenic miRNA biogenesis expands our understanding of colon cancer cell biology and identifies novel therapeutic targets.